(Class Management in Fostering Early Childhood Interest in Learning at Insan Kaamil Teniga Kindergarten) - Eliyana, Eliyana; Ramzi, Muhajirin (JUPE : Jurnal Pendidikan Mandala, 2024)
This research aims to describe Class Management in Fostering Children's Interest in Learning at Insan Kaamil Teniga Kindergarten. The method used in this research is a qualitative research approach and a descriptive research type. This research aims to describe everything related to classroom management in fostering children's interest in learning. The results of the research show that children's interest in learning can be fostered by several things, including Insan Kaamil Kindergarten teachers designing the class, arranging tables and chairs according to the child's wishes, paying more attention to the child, controlling the class atmosphere, making games or quizzes in between studying, and supported by media that is appropriate to the theme to be conveyed so that children feel happy, are interested in learning, and show attention when learning takes place.